Delivering a dietetic intervention to cardiovascular patients in the Covid era. (11th May 2021) - Rodgers, A; Edwards, W; Garrity, J; Latimer, D; Wilson, D; Connolly, S
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Department of Health Introduction: Healthy diet and body composition are core components of cardiac rehabilitation. Following the COVID outbreak in March 2020, our face-to-face cardiac rehabilitation programme (Our Hearts Our Minds) was suspended. The programme was then quickly moved to a virtual platform to continue to deliver the programme. Purpose Here we describe how the OHOM programme adapted our service to deliver the dietetic assessment and intervention on a virtual platform. Methods: Pre-Covid the dietary component of OHOM consisted of a face-to-face Initial Assessment (IA) with a dietitian, group education sessions and an End of Programme assessment (EOP). Anthropometric measures and dietary habits were assessed including adherence to the Mediterranean diet via the Mediterranean Diet Score (MDS) toolkit. Using behaviour change techniques, tailored dietary advice was provided and goals agreed to educate on healthier food choices, increase adherence to Mediterranean diet and (if appropriate) promote weight loss and reduce central obesity. The assessment and intervention is now delivered virtually via telephone or video. Anthropometrics are self-reported with tape-measures supplied to assess waist circumference and advice provided on home-weighing. MDS is still assessed. The programme includes fortnightly coaching telephone consultations to review and reset goals, the option to attend a dietitian-led virtual group education session, access to a filmed educational video and submission of food diaries via the Fitbit app. Results: From April to November 2020, 114 patients completed the virtual programme (65 telephone, 39 video). Dietetic outcomes are outlined in Table 1 with inclusion of data for a similar period one year previously (face-to-face) for comparison. Reductions in anthropometric measures and increased adherence to a cardio-protective diet were noted and the results for the two time periods are remarkably similar. Conclusion: Delivery of a virtual dietetic component in cardiac rehabilitation is feasible, acceptable and just as effective as face-to-face based on preliminary data.